Les generations des Soufis : Ṭabaqāt al-ṣūfiyya de Abū ʻAbd al-Raḥmān, Muḥammad born Ḥusayn al-Sulamī (325/937-412/1021) - Sulamī, Muḥammad ibn al-Ḥusayn, -1021, (Studies on Sufism, 2019)
In his book Generations of Sufis , Abū ʿAbd al-Raḥmān al-Sulamī (died 1021), the Sufi master of Nishapur and Shafiʿi traditionist and historian, collected the teachings of 105 Sufi masters who lived between the 2nd/8th and the 4th/10th centuries. Sulami gives a short biography of each master with representative quotations from his teachings. He thereby illustrates the numerous approaches to the spiritual path and the unity of its principles. One of the oldest works of the sort, it assembles the doctrinal foundations from which medieval Sufism developed. It is a key reference which influenced all Sufi literature and even historiography. This is the first translation of a work of this type to be published in a European language. Dans Les générations des Soufis Abū ʿAbd al-Raḥmān al-Sulamī (m. 1021), maître soufi de Nishapur, traditionniste šāfiʿite et historien, collecte l'enseignement de cent cinq maîtres soufis qui vécurent entre le 2e/8e et le 4e/10e siècles. Pour chacun d'eux, Sulamī propose une courte notice biographique et un ensemble de citations représentatives de son enseignement. Il rend ainsi compte de la diversité des approches de la voie spirituelle et de l'unité de ses principes. Cet ouvrage, l'un des plus anciens de ce type, rassemble le socle doctrinal sur lequel s'élabora le soufisme médiéval. Référence incontournable, il eut une influence considérable sur toute la littérature du soufisme et même l'historiographie. Cette traduction est la première en langue européenne d'un ouvrage de ce type.